Aspek Sosial pada Materi Sastra di Buku Bahasa Indonesia Tingkat Lanjut SMA Kelas XI dan Relevansinya dengan P5 (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the social transformations found in the literary aspects of the Advanced Indonesian Language Textbook for grade 11 and analyze its relationship to the construction of the Pancasila Student Profile (P5). The main focus of this study is to examine how the literary works presented in the textbook function not only as a medium for language learning but also as a vehicle for character development and social understanding for students. This study uses a descriptive qualitative approach with sociological literary analysis techniques, where data is obtained from excerpts from poetry, short stories, and plays that depict social change. The results indicate that the social transformations reflected in these literary works are divided into two main forms: collective behavior and social movements. Collective behavior is demonstrated through themes of fashion and fashion, urban legends, and the phenomenon of mass hysteria, which implicitly depict social conflict, class inequality, and the dynamics of societal culture. Meanwhile, social movements are depicted in the narratives of characters who fight for change against norms, traditions, and social structures that limit freedom. This representation demonstrates resistance, critical awareness, and a drive towards a more just and equal life. The findings of this study are closely related to the dimensions of the Pancasila Student Profile, such as critical reasoning skills, a spirit of mutual cooperation, an attitude of upholding social justice, and independence in thought and action. Therefore, it can be concluded that literary works in Indonesian language textbooks not only present aesthetic value and literary appreciation, but also serve as an effective means of instilling national values and supporting the formation of student character in accordance with the vision of Pancasila.